Когнитивная семантика и нарративные функции парентезы „кажется” в разных контекстах художественного дискурса - Чернцова, Елена (Studia Rossica Posnaniensia, 2017)
This article analyzes the cognitive semantics of the parenthesis кажется, as well as its functions in developing a fictional narrative strategy. The analysis shows that the parenthesis кажется does not have its own conceptual value and it is functionally related to the subject's reflection on cognitive activity, whose contents are predetermined by various perspectives of the context. The semantics and narrative functions of the parenthesis кажется are identified within such parameters as ‘communicative logic of the cognitively active subject’, ‘subjective structure of context’, along with a ‘communicative register’ — ‘reproductive’ or ‘informative’ — and a ‘narrative strategy’.